The Effect Of Total Asset Turnover (TATO) And Net Profit Margin (NPM) On Return On Assets (ROA) At PT Mustika Ratu TBK For The 2015-2024 - Febriyani, Fitri; Fadli, Achmad Agus Yasin (Jurnal Fokus Manajemen, 2025)
This study aims to determine the effect of Total Asset Turnover and Net Profit Margin on Return On Asset at PT Mustika Ratu tbk 2015-2024. Both partially and silently. The population of this study uses secondary data obtained from the annual financial statements of PT Mustika Ratu, Tbk during the period 2015-2024. This study is a descriptive analysis study with a quantitative method approach. The data collection technique in this study uses classical assumption test techniques, namely in the form of normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The data analysis technique in this study uses multiple linear regression analysis. Based on the results of the study, the total asset turnover was partially unaffected, there was no significant influence on the Return On Asset with a t-calculated value that was smaller than the t-table value, which was -0.394 < 2.306, and a significance value of 0.705 > 0.05. In the Net Profit Margin variable, there is a significant influence on Return On Asset with a t-calculated value greater than the t-table of 35.898 > 2.306 and a significance value of 0.000 < 0.05. Together, Total Asset Turnover and Net Profit Margin have a positive and significant effect on Return On Asset with an F-calculated value greater than the F-table value of 830,303 > 4.74 and a significance value of 0.000 < 0.05.